La désintégration yougoslave : un cadre fertile pour la théorie des dominos ? - Gagnon, Rémy (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Undoubtedly, one of the most critical crisis in the post-Cold War ex a, the Yugoslav conflict, due to its nationalist character, nurture the fear that a full scale Balkan War would result. In the very heart of Europe, it threated to spread, and then to slip away from the Occidental power's control. How to explain it, but specially how to prevent this diffusion ? The Domino Theory applied to the Yugoslav conflict proposes a model to answer these core questions. Based on a positive model of spatial diffusion, the analysis which follows investigates in depth the relationships between the « 1989 socialist break-up », the internal situation of Yugoslavia, and the spreading of the conflict. By so doing this analysis sheds light on the circomstantial causes and on the chaine of events which explain the origin of the conflict, as well as its expension. Starting with the postulate that the actions of state, within a given spatial and time framework, have a definite chance of influencing the actions of its neighboring states, we attribute an important mesure of responsibility to the collapse of USSR in the Yugoslav Conflict's release.